Ultrastructure of novel thrombocytes in the dog snapper Lutjanus jocu. Issue 4 (7th March 2014) - Azevedo, C.; Matos, P.; Rocha, S.; Matos, E.; Oliveira, E.; Al‐Quraishy, S.; Casal, G.
<x xml:space="preserve">Abstract</x> Myxosporean cysts containing spores of Henneguya sp. were observed in the gills of the dog snapper Lutjanus jocu. Adjacent to the cysts were capillaries, allowing observation of peripheral blood cells. Numerous white blood cells displaying uncommon cytoplasmic projections were observed amongst the erythrocytes. Their morphology allowed them to be identified as thrombocytes (TCs). Each TC displayed 18–26 cytoplasmic projections, most of which were in close proximity to erythrocytes. At their apical end, each cytoplasmic projection presented an ellipsoidal vacuole (c. 0·6 µm × 0·3 µm) from which a secretory tubule, 0·3–0·4 µm long and c. 120 nm in total diameter, extended towards the periphery of the TC plasmalemma and fused with the cellular membrane. From this opening, contents of vacuoles were apparently released into the lumen of the capillaries. Other vacuoles with similar features, and containing an electron‐lucent matrix, were observed in the cytoplasm of the TC. This is the first description of fish TC with these ultrastructural features and organization, which suggest that they perform a secretory function.